2018
DOI: 10.1371/journal.pone.0205242
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3/Caspase-1 inflammasome activation is decreased in alveolar macrophages in patients with lung cancer

Abstract: Lung cancer (LC) remains the leading cause of cancer-related mortality. The interaction of cancer cells with their microenvironment, results in tumor escape or elimination. Alveolar macrophages (AMs) play a significant role in lung immunoregulation, however their role in LC has been outshined by the study of tumor associated macrophages. Inflammasomes are key components of innate immune responses and can exert either tumor-suppressive or oncogenic functions, while their role in lung cancer is largely unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 66 publications
3
23
0
Order By: Relevance
“…Consistently, reduced NLRP3-dependent IL-1β secretion is observed in AMs isolated from the bronchoalveolar lavage of lung cancer patients despite a systemic higher NLRP3 inflammasome activation and IL-1β secretion in peripheral blood leukocytes from these patients [230,231]. Thus, the elevated IL-1β concentration in TME [232] could either derive directly from oncogenic lung cancer cells [233] or eventually from another TAM population (i.e., infiltrated MoTAMs) [230]. In the first scenario, combination of canakinumab with anti-PD-1 therapy, as initiated in phase I trial, may be beneficial by dual targeting of cancer and immune cells.…”
Section: Il-1β Signaling and Immunometabolism: A New Role In Lung mentioning
confidence: 75%
See 1 more Smart Citation
“…Consistently, reduced NLRP3-dependent IL-1β secretion is observed in AMs isolated from the bronchoalveolar lavage of lung cancer patients despite a systemic higher NLRP3 inflammasome activation and IL-1β secretion in peripheral blood leukocytes from these patients [230,231]. Thus, the elevated IL-1β concentration in TME [232] could either derive directly from oncogenic lung cancer cells [233] or eventually from another TAM population (i.e., infiltrated MoTAMs) [230]. In the first scenario, combination of canakinumab with anti-PD-1 therapy, as initiated in phase I trial, may be beneficial by dual targeting of cancer and immune cells.…”
Section: Il-1β Signaling and Immunometabolism: A New Role In Lung mentioning
confidence: 75%
“…While macrophages are the main source of IL-1β secretion in the immune response to pathogen [226,227,228], the TME of established tumors is characterized by an immunosuppression dominated by a M2 alternatively activated TAM phenotype that inhibits NLRP3-dependent IL-1β secretion [229]. Consistently, reduced NLRP3-dependent IL-1β secretion is observed in AMs isolated from the bronchoalveolar lavage of lung cancer patients despite a systemic higher NLRP3 inflammasome activation and IL-1β secretion in peripheral blood leukocytes from these patients [230,231]. Thus, the elevated IL-1β concentration in TME [232] could either derive directly from oncogenic lung cancer cells [233] or eventually from another TAM population (i.e., infiltrated MoTAMs) [230].…”
Section: Il-1β Signaling and Immunometabolism: A New Role In Lung mentioning
confidence: 99%
“…IL-1β is involved in NSCLC progression and may be involved in immunosuppression and in promoting NSCLC development. 29 A study proposed the possibility that anti-inflammatory therapy by targeting IL-1β may reduce the prevalence of lung cancer among patients who have higher CRP. 30 Recently, a phase 3 clinical trial has reported an interesting result, anakinumab, an inhibitory antibody targeting IL-1β, could significantly reduce the incidence and mortality of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tumor-associated macrophages isolated from lung tumor bearing mice exhibited increased production of IL-1β when stimulated with LPS plus ATP 58 . Similarly, peripheral blood leukocytes from patients with primary lung cancer released more IL-1β and IL-18 than did those from healthy individuals 59 . In addition, an important role of IL-1β derived from neutrophils was elucidated in relation to the impaired efficacy of NF-κB inhibitor against lung carcinogenesis 60 .…”
Section: Involvement Of the Inflammasomes And Their Effector Moleculementioning
confidence: 91%